Affinity-matured 'aquaporumab' anti-aquaporin-4 antibody for therapy of seropositive neuromyelitis optica spectrum disorders. (1st January 2020) - Duan, Tianjiao; Tradtrantip, Lukmanee; Phuan, Puay-Wah; Bennett, Jeffrey L.; Verkman, Alan S.
Abstract: Pathogenesis in seropositive neuromyelitis optica spectrum disorders (herein called NMO) involves binding of IgG1 autoantibodies to aquaporin-4 (AQP4) on astrocytes in the central nervous system, which initiates complement and cellular injury. We previously developed an antibody blocking approach for potential therapy of NMO in which an engineered, monoclonal, anti-AQP4 antibody lacking cytotoxicity effector functions (called aquaporumab) blocked binding of NMO autoantibodies to astrocyte AQP4 (Tradtrantip et al. Ann. Neurol. 71, 314–322, 2012). Here, a high-affinity aquaporumab, which was generated by affinity maturation using saturation mutagenesis, was shown to block cellular injury caused by NMO patient sera. Anti-AQP4 antibody rAb-53, a fully human antibody with effector function neutralizing Fc mutations L234A/L235A and affinity-enhancing Fab mutations Y50R/S56R, called AQmab AM, bound to AQP4 in cell cultures with Kd ~ 18 ng/ml (~0.12 nM), ~8-fold greater affinity than the original antibody. AQmab AM, but without L234A/L235A Fc mutations, produced complement-dependent cytotoxicity (CDC) with EC50 ~ 82 ng/ml. AQmab AM prevented CDC produced by sera from eight NMO patients with IC50 ranging from 40 to 80 ng/ml, and similarly prevented antibody-dependent cellular cytotoxicity (ADCC). Mechanistic studies demonstrated that AQmab AM blocked binding of serum NMO autoantibodies to AQP4. AQmab AM offers a targeted, non-immunosuppressive approach for therapy of seropositive NMO. Autoantibody blocking may be a useful therapeutic strategy for other autoimmune diseases as well. Highlights: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory disease of the central nervous system. Seropositive NMOSD is caused by binding of pathogenic IgG autoantibodies to water channel aquaporin-4 on astrocytes. Aquaporumab is an engineered human monoclonal IgG antibody, with effector functions neutralized, that strongly binds to aquaporin-4. An affinity matured aquaporumab blocked NMOSD autoantibody binding to aquaporin-4 and prevented complement and cellular cytotoxicity.